Analisis Kuantitatif Hasil Belajar Melalui Mindfulness dan Kecerdasan Emosional Pada Siswa Sekolah Minggu Buddha di Tangerang Selatan - Ida Bagus Dharmika; Willie Japaries; Adriana Venny Ariani; I Nyoman Susila Karyasta; Handi Chandra (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
Learning process This is on the Students School Buddhist Week in South Tangerang, from observation writer results Study from students Still Not yet in accordance with the hopes of educators, because Still problems with understanding, attitudes , values , skills , practice of Dhamma. By theoretical writer use reference from outside and inside as well as from Buddhism Dhamma teachings . Study This use approach quantitative purpose for know the influence of Mindfulness and Intelligence Emotional on Learning Outcomes Student School Buddhist Week in South Tangerang. Study This done at the Vihara or Cetiya in South Tangerang, with subject study is 170 students School Buddhist Week. Research analysis methods. This use help SPSS version 26. Analysis results show that There is influence positive and significant between Mindfulness (X1), Intelligence Emotional (X2) on Learning Outcomes (Y). Regression equation Ŷ 3= 46.605 + 0.534X 1 + 0.112X 2, with score coefficient correlation generated of r y1,2 = 0, 661 , whereas score coefficient determination generated as big as r 2 x1,2 = 0.436 , meaning donation or influence amounting to the remaining 43.6% amounting to 56.4% was contributed by other variables that have connection positive with increasing Learning Outcomes .